On *-wildness of a free product of finite-dimensional C^*-algebras - Sukretniy, K.; Jushenko, E. (Methods of Functional Analysis and Topology, 2006)
In this paper we study the complexity of representation theory of free products of finite-dimensional C^*-algebras.